Connecticut's Family Assessment Response system. Issue 4 (8th August 2021) - Carlson, Patricia M.; Feely, Megan; Kurz, Brenda; Lin, Hsiu-Ju; Ives, Melissa; Pierce, Joshua; Rogers, Elliot; Nilson, Kimberly
ABSTRACT: This study describes the family characteristics, prevalence of risk factors, and explores factors associated with subsequent and substantiated subsequent reports of child abuse/neglect for the differential response track in Connecticut, Family Assessment Response (FAR). Results indicated that while relatively low risk, FAR serves families with significant issues. The results underscore the need for accessible and effective mental health and behavioral health interventions for caregivers. Additionally, more thorough risk assessments are needed to better understand the families served. Measures of poverty are needed to discern how poverty and caregiver and child risk factors interact.